REPEAT OF WORDS IN THE POETRY OF ABDUVALI QUTBIDDIN - Iminjanov Boburmirzo Xabibullo o’g’li (European Science Publishing, 2024)
This article talks about the creative views of the poet and publicist Abduvali Qutbiddin, the peculiarities of his poems, in particular, how he achieved melodiousness through the repeated use of words. By giving examples of some of the poet's poems, these characteristics are shown in a more open and clear way. The main attention is focused on repeated expressions in the poet's poems.
Keywords: Poem, lover, Shavkat Rahman, Homeland, Osima, signs, grouping, love.